Size distributions and sex ratios of sharks caught by Oman’s artisanal fishery - Henderson, A.; McIlwain, Jennifer; Al-Oufi, H.; Al-Sheile, S.; Al-Abri, N. (National Inquiry Services Centre, 2009)
Oman’s fishery resources are exploited by artisanal and industrial fisheries, but the former accounts for almost 90% of landings. Within the artisanal fishery, sharks have traditionally been harvested for their flesh, but the development of a valuable export market for shark fin has led to increased utilisation of this resource, and anecdotal information suggests that shark abundance has decreased in recent years. Whereas management of the shark fishery is desirable, the biological and socio-economical data on which to base any management plan are lacking. The present study was undertaken to collect size frequency and sex ratio information from the shark species most commonly encountered in the artisanal landings, namely Carcharhinus falciformis, C. limbatus, C. macloti, C. sorrah, Iago omanensis, Loxodonmacrorhinus, Rhizoprionodon acutus and Sphyrna lewini. The occurrence of large female sharks in the landings, combined with a high proportion of juveniles of certain species, suggests that speciesspecific size restrictions should be considered in any management plan for Oman’s shark fishery.